2011
DOI: 10.1128/aac.01222-10
|View full text |Cite
|
Sign up to set email alerts
|

Resistance and Tolerance to Tropodithietic Acid, an Antimicrobial in Aquaculture, Is Hard To Select

Abstract: The antibacterial compound tropodithietic acid (TDA) is produced by bacteria of the marine Roseobacter clade and is thought to explain the fish probiotic properties of some roseobacters. The aim of the present study was to determine the antibacterial spectrum of TDA and the likelihood of development of TDA resistance. A bacterial extract containing 95% TDA was effective against a range of human-pathogenic bacteria, including both Gram-negative and Gram-positive bacteria. TDA was bactericidal against Salmonella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
72
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 47 publications
2
72
0
Order By: Relevance
“…Specifically, strains belonging to the species Ruegeria mobilis and Phaeobacter inhibens are potent antagonists of the fish pathogens (Planas et al, 2006;Porsby et al, 2008;D'Alvise et al, 2010) primarily caused by production of the antibacterial compound tropodithietic acid (TDA) (D'Alvise et al, 2010(D'Alvise et al, , 2012. TDA is also bactericidal against human pathogens including Salmonella enterica and Staphylococcus aureus (Porsby et al, 2011) and it has been recently been demonstrated that TDA acts by disrupting the proton motive force (Wilson et al, 2016). TDA is produced by R. mobilis, P. inhibens and Phaeobacter gallaeciensis, as well as by other alphaproteobacteria belonging to Pseudovibrio (Porsby et al, 2008;Geng and Belas, 2010;Penesyan et al, 2011;Harrington et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, strains belonging to the species Ruegeria mobilis and Phaeobacter inhibens are potent antagonists of the fish pathogens (Planas et al, 2006;Porsby et al, 2008;D'Alvise et al, 2010) primarily caused by production of the antibacterial compound tropodithietic acid (TDA) (D'Alvise et al, 2010(D'Alvise et al, , 2012. TDA is also bactericidal against human pathogens including Salmonella enterica and Staphylococcus aureus (Porsby et al, 2011) and it has been recently been demonstrated that TDA acts by disrupting the proton motive force (Wilson et al, 2016). TDA is produced by R. mobilis, P. inhibens and Phaeobacter gallaeciensis, as well as by other alphaproteobacteria belonging to Pseudovibrio (Porsby et al, 2008;Geng and Belas, 2010;Penesyan et al, 2011;Harrington et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…TDA is a broad-spectrum antibacterial that is bactericidal and inhibits the growth of several human and fish pathogens (16,(21)(22)(23) but has very low toxicity in Caenorhabditis elegans and Artemia (24). Recently, it was demonstrated that TDA is cytotoxic against N2a cells and OLN-93 cells of the mammalian nervous system and several cancer cell lines, respectively (25,26).…”
mentioning
confidence: 99%
“…Since TDA has pronounced antibacterial activity, the development of resistance to TDA could be a concern, especially following long-term use. Attempts to select for TDA resistance and tolerance in pathogenic bacteria have not been successful (22), suggesting that TDA resistance does not arise easily, likely due to a highly conserved target (or targets). Very recently, Wilson et al demonstrated that cell membranes and the proton motive force (PMF) were targets of TDA, and TDA was suggested to function as an electroneutral proton antiporter, facilitating a one-to-one exchange of H ϩ for a single charged metal ion and thus disrupting the transmembrane proton gradient (⌬pH) (26).…”
mentioning
confidence: 99%
“…in turbot larval farms was found to suppress growth of marine pathogens such as Vibrio anguillarum (37) and enhanced survival of the larvae (45). Thus, the use of these roseobacters as probiotics in aquaculture facilities (25,36,38) or as antifouling agents in marine systems (15,40) is of great interest.…”
mentioning
confidence: 99%